Low concentration press cake protein isolates preserve biological activity during lyophilization and spray drying - Egger, Kristina; Schenzle, Lisa; Isabel, Afonso Urich Andreina; Zettl, Manuel; Fuchs, Aleksandra; Pichler, Harald (Frontiers in Nutrition, 2025)
A primary challenge in bringing cultivated meat to the market is the high cost of the cell culture media, largely due to their reliance on serum albumins. The production of these albumins is anticipated to become a major bottleneck of this industry. Recently, human serum albumin (HSA) was successfully substituted with seed protein isolates from press cakes enriched with plant albumins. However, these isolates require storage at -80°C to maintain activity, as long-term storage at 4°C or lyophilization leads to aggregation and loss of biological activity. Here, we show that concentrated protein isolates from Styrian oil pumpkin can effectively substitute for human serum albumin (HSA) and support higher proliferation rates in short term experiments as compared to HSA when stored at -80°C (p < 0.001), or even when lyophilized (p < 0.01). We also demonstrate that protein isolates from Styrian oil pumpkin and rapeseed press cakes perform comparably to HSA (no significant differences) when lyophilized or even spray-dried, provided that the concentration step is omitted. Furthermore, we report protein yields that are four times higher when a more thorough grinding method is utilized. These advancements eliminate the necessity for -80°C storage, thereby facilitating the utilization of locally available press cake protein isolates in media stabilization applications.